Analytical platform for the process of managing the flows of secondary resources in the construction industry - Shuvaiev, A.A. (Ways to Improve Construction Efficiency, 2023)
The scientific article reveals the problems of finding innovative approaches to solving optimization problems related to the management of flows of secondary resources-materials for the implementation of construction processes. Promising trends of logistic concepts as an important tool for effective management of flows of secondary resources in the construction sector are studied. The urgency of the problem of finding rational solutions in managing the flows of secondary resources (materials) in the context of construction Processes. The publication highlights the main regularities of functioning of the system of integrated management of waste flows (SKUPV) in the construction industry and identifies the practical possibilities of their implementation. A scheme for finding optimal solutions based on the principles of logistics systems is outlined. The prospects and possibilities of using construction waste as secondary resources-materials are substantiated. As a result of the analysis, it was found that building production systems, while developing, have undergone an optimization evolution and reached a new, progressive level of flow management. The proposed approach assumes that material and energy resources are not concentrated in the final product, but are accumulated in the form of additional products – raw materials and energy, which are reused in the recycling process in their own production or sold in secondary markets. The results of the study made it possible to reveal the definition of the system of integrated management of waste flows (ICMS) of the construction industry, which takes into account the key components of the economic effect. It is an indisputable fact that the waste of the construction industry has a significant potential to become a secondary raw material, the use of which after processing (as secondary products) according to certain technologies (which are becoming more and more in the context of the search for environmentally friendly organizational and technological solutions), allows to reduce the cost of construction projects and at the same time reduce the load on landfills, to exclude the uncontrolled increase in unauthorized landfills. It should also be noted that as a result of the processing of waste from the dismantling of structures using advanced technologies based on the principles of environmentally oriented innovative development, the efficiency of the use of materials increases by reducing production costs.